2020
DOI: 10.1136/sextrans-2019-054290
|View full text |Cite
|
Sign up to set email alerts
|

Levels of anxiety and distress following receipt of positive screening tests in Australia’s HPV-based cervical screening programme: a cross-sectional survey

Abstract: ObjectiveFrom December 2017, the Australian National Cervical Screening Program commenced 5 yearly primary human papillomavirus (HPV) screening; one of the first high-income countries to implement primary HPV screening. This study aimed to examine the psychosocial impact of self-reporting testing HPV positive in a sample of women screened since the renewal of the programme.MethodsWomen in Australia aged 25–74 years who reported participating in cervical screening since December 2017 were recruited through an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 25 publications
6
24
4
Order By: Relevance
“…Principally, the increased specificity of dual‐stained cytology can lead to increased efficiency of cervical cancer screening by implementing an additional diagnostic tool for triaging management of patients with positive high‐risk HPV, which can reduce colposcopy and histology rates and, consequently, excessive diagnosis. Our results can ultimately guide the implementation of primary HPV screening in Canada, reduce costs and potentially reduce psychological anxiety and distress 37 associated with the diagnosis of a sexually transmitted infection in women not adequately informed about the natural history of HPV.…”
Section: Discussionmentioning
confidence: 91%
“…Principally, the increased specificity of dual‐stained cytology can lead to increased efficiency of cervical cancer screening by implementing an additional diagnostic tool for triaging management of patients with positive high‐risk HPV, which can reduce colposcopy and histology rates and, consequently, excessive diagnosis. Our results can ultimately guide the implementation of primary HPV screening in Canada, reduce costs and potentially reduce psychological anxiety and distress 37 associated with the diagnosis of a sexually transmitted infection in women not adequately informed about the natural history of HPV.…”
Section: Discussionmentioning
confidence: 91%
“…9 Previous research has demonstrated a number of negative psychosocial impacts for women testing HPV+ including anxiety and distress, 10 11 feelings of stigma, embarrassment and confusion, as well as concerns about their sexual relationships in terms of trust, fidelity and blame due to concern about the sexually transmitted nature of HPV. 12 Findings from our previous study which surveyed over 1000 women in Australia, also showed women who tested HPV+ were more anxious and distressed than those who tested HPV-, 13 with anxiety scores 10 points higher than those found in a recent English study. 5 As most research to date has been quantitative and conducted prior to implementing the NCSP changes, there is a need for in-depth qualitative exploration of women's views and experiences of the renewed NCSP in the year since its implementation.…”
Section: Introductionmentioning
confidence: 80%
“…Our own survey data has shown anxiety and distress were higher in women who did not know their results compared with those who were HPV-. 13 The recommendations provided by the women in this sample for information delivery to be staged across the screening journey, from prior to screening to receiving the results, are important to consider when implementing a new screening test to help women’s understanding of both the reasons for the new test and what the results of the new test mean for them. Women have been shown to prefer active or shared decision-making approaches regarding the follow-up of abnormal test results, 22 so it is important women understand what these results mean for them.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the prevalence rate of hrHPV was 13.7% on self-collected samples. The high prevalence of hrHPV not only leads to unnecessary colposcopy or follow-up burden [9], but also might add to the mental burden of the HPV-positive women [17]. However, in HPVbased screening programs, there is still no consensus on the optimal management of HPVpositive women to maximize disease detection and minimize colposcopy rates [18,19].…”
Section: Discussionmentioning
confidence: 99%